Evaluation of a small flat rectangular therapeutic ultrasonic transducer intended for intravascular use - Papadopoulos, Nikolaos; Menikou, Georgios; Yiannakou, Marinos; Yiallouras, Christos; Ioannides, Kleanthis; Damianou, Christakis A. (My University, 2017)
.Background The aim of the proposed study was to evaluate the performance of a flat rectangular (2 × 10 mm2) transducer operating at 4 MHz. The intended application of this transducer is intravascular treatment of thrombosis and atherosclerosis. Methods The transducer's thermal capabilities were tested in two different gel phantoms. MR thermometry was used to demonstrate the thermal capabilities of this type of transducer. Results Temperature measurements demonstrated that this simple and small transducer adequately produced high temperatures, which can be utilized for therapeutic purposes. These high temperatures were confirmed using thermocouple and MR measurements. Pulsed ultrasound in combination with thrombolytic drugs and microbubbles was utilized to eliminate porcine thrombi. Conclusions The proposed transducer has the potentials to treat atherosclerotic lesions using the thermal properties of ultrasound, since high temperatures can be achieved in less than 5 s. The results revealed that the destruction of thrombi using pulsed ultrasound requires long exposure time and high microbubble dosage.
Keywords: Atherosclerosis; Intravascular; Thrombosis; Ultrasound